PENYUSUNAN COFFEE TABLE BOOK UNTUK MENGENALKAN KEKAYAAN BATIK BANYUMAS KEPADA GENERASI MILENIAL: COMPILATION OF A COFFEE TABLE BOOK TO INTRODUCE THE RICHNESS OF BANYUMAS BATIK TO THE MILLENNIAL GENERATION - Steven Enrico Raharjo; Elizabeth Susanti; Jessica Yonatia (Jurnal Dimensi Seni Rupa dan Desain, 2025)
Batik is an Indonesian culture that is full of richness. Throughout Indonesia, various types of batik are found with distinctive motifs and techniques, reflecting the history, culture, and traditions of the local community. One of the regions in Indonesia that has extraordinary batik wealth is Banyumas, located in Central Java. Banyumas batik is a cultural heritage that has a cultural acculturation, namely inland batik and coastal batik, each of which has a long historical influence, unique motifs, and distinctive craftsmanship techniques. The purpose of this study is to design a coffee table book that can effectively introduce Banyumas Batik culture to the millennial generation. The method of field observation and structured interviews with sources with William Kwan Hwie Liong to obtain primary data on the characteristics of Banyumas batik and its history, and the distribution of questionnaires was carried out online to 100 millennials to obtain secondary data. The results of the study are a coffee table book that shows the importance of introducing the richness of Banyumas batik to the millennial generation and using aesthetic and attractive visual elements so that they can be more interested.